PENERAPAN MODEL LEARNING CYCLE UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V C SD NEGERI 163 PEKANBARU - Astri, Yulani Nur; Alpusari, Mahmud; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was conducted because of the result of learning science study grade V C SD Negeri 163 Pekanbaru. KKM achieved by school was 72. From 40 students who achieve KKM just 13 students (32,50%) while students who did not achieve KKM is 27 students (67,50%) with a grade average of 61,35. The purpose of this research to improve learning outcomes IPA class V C SD Negeri 163 Pekanbaru with the application of models Learning Cycle. The results obtained by the average value of 61,35 basic score increased in the first cycle of 23 % to 75,50. In the second cycle the average value of students also increased by 43% to 88,20. On the basic of classical completeness score IPA student learning outcomes is only 32,50% (not finished). After the process of application learning model Learning Cycle in the first cycle classical completeness increased to 75% (not finished), and the second cycle of classical completeness obtained are increased to increase to 95% (finished). Activities of teachers at the first meeting of first cycle acquire a percentage of 75% with enough categories. The second meeting increased to 80% in good categories. In the first meeting of second cycle increased to 90% with very good category. At the second meeting increased to 95% with very good category. Activities of students in the first meeting of the first cycle acquire a percentage of 75% with enough categories. The second meeting increased to 85% in good categories. In the first meeting of the second cycle increased to 90 % with very good category. At the second meeting increased to 95% very good category. This the implementation of learning cycle model can improve student learning outcomes IPA.Keywords: Learning Cycle, Learning Outcomes IPA